Pharmacy as a Catalyst for Healthcare Transformation: Integrative Practices to Optimize Patient Care - Mohammed Debshan Mogram Al-Ahmari, Alanoud Ali Abdullah Asiri, Maha Mufareh Ali Assiri, Waleed Ibrahim Mohammed Hamithi, Mohammad Ali Manea Aljaezi; Abdulrahman Ali Mohammed Asiri, Abdulrahman Awad Mushabbab Alahmari, Ali Hassan Ali Sulaiman, Zayed Ali Mohammed Alzawani, Saeed Mohammed Abdullah Alqahtani (Journal of International Crisis and Risk Communication Research, 2024)
Pharmacy has emerged as a pivotal discipline in the evolving healthcare landscape, with pharmacists taking on more integral roles beyond traditional medication dispensing. The integration of pharmacy into multidisciplinary healthcare teams, particularly in the realms of patient care optimization, medication management, and preventive health services, is transforming healthcare delivery systems. This paper explores how pharmacy can act as a catalyst for healthcare transformation, focusing on integrative practices that enhance patient outcomes, reduce healthcare costs, and improve overall quality of care. By examining collaborative models of care, pharmacist involvement in chronic disease management, medication therapy management (MTM), and patient education, this paper highlights how the evolving role of pharmacists is essential in shaping the future of healthcare.